An Analysis on Determinants of Cash and L/C Export: Findings from Türkiye’s Export - Ahmed Yusuf Sarıhan (Cumhuriyet Üniversitesi İktisadi ve İdari Bilimler Dergisi)
The payment methods used in international trade are of significant importance for the financial flow of the involved parties. When it comes to transferring goods and funds across borders to their new owners, the risks faced by the parties may seem daunting. The use of a letter of credit payment method by banks serves a protective role, enabling the parties to engage in trade more securely. While the expenses linked to this approach are sometimes viewed as challenging for the involved parties, it is considered a significant enabler, particularly in new trade alliances. In fact, exporters' choices are classified in countries' trade statistics based on payment methods. This study aims to uncover the determinants of exports from Türkiye between January 2013 and September 2023, utilizing both cash in advance and letter of credit payment methods. To accomplish this objective, exchange rates and specific inflation indicators, and their causal relationship with export transactions based on payment types was examined using the Toda-Yamamoto causality test. The research findings indicate that exchange rates, inflation, and cash payment variables cause letter of credit payments. Conversely, only the foreign producer price index was identified as a cause for cash-based exports. These findings illustrate that economic indicators, which may pose risks for Turkish exporters, are reasons for important decisions. In light of these findings, recommendations have been made for exporters and policymakers to proceed cautiously in the face of different economic scenarios.